Targeting platelet receptors in thrombotic and thrombo-inflammatory disorders - Vögtle, T.; Cherpokova, D.; Bender, M.; Nieswandt, B. (Hämostaseologie, 2015)
Platelet activation at sites of vascular injury is critical for the formation of a hemostatic plug which limits excessive blood loss, but also represents a major pathomechanism of ischemic cardio- and cerebrovascular diseases. Although currently available antiplatelet therapies have proved beneficial in preventing the recurrence of vascular events, their adverse effects on primary hemostasis emphasize the necessity to identify and characterize novel pharmacological targets for platelet inhibition. Increasing experimental evidence has suggested that several major platelet surface receptors which regulate initial steps of platelet adhesion and activation may become promising new targets for anti-platelet drugs due to their involvement in thrombotic and thrombo-inflammatory signaling cascades.This review summarizes recent developments in understanding the function of glycoprotein (GP)Ib, GPVI and the C-type lectin-like receptor 2 (CLEC-2) in hemostasis, arterial thrombosis and thrombo-inflammation and will discuss the suitability of the receptors as novel targets to treat these diseases in humans.
Keywords: Platelets; thrombus formation; platelet receptors; antithrombotic target